Pengembangan Alat Ukur Skala Citra Tubuh - Aina Putri Khairani; Hannan Hannan; Laura Amalia (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2019)
This study aims to test the validity and develop body image scale measurement tools. The development of this measuring instrument is based on Cash's theory (2012) which consists of 5 aspects namely appearance evaluation, appearance orientation, satisfaction with body parts, anxiety of being fat and categorizing body size. Respondents in this study numbered 196 vocational students in the District of West Semarang with cluster random sampling technique. From the EFA obtained KMO value of 0.762 and experienced changes in aspects into 2 aspects namely appearance evaluation and satisfaction with appearance.